Representations of antiquity in film: from Griffith to grindhouse - McGeough, Kevin M. (Discourses in ancient Near Eastern and biblical studies, 2022)
"Representations of Antiquity in Film offers an introduction to how the ancient world is represented in film and especially Hollywood cinema. By considering cinematic narrative as well as various elements of film design, McGeough presents a comprehensive overview of the topic designed for students and scholars with varying backgrounds in media studies, archaeology, religious studies, and ancient history"--